Turn-Taking Strategies Analysis in Conversation between President Jokowi and Boy William in Nebeng Boy Youtube Channel - Yanti Kristina Sinaga; Arwin Tannuary; Nanda Saputra (Britain International for Academic Research (BIAR-Publisher), 2021)
The aims of this study were to identify the types and the most dominant of turn-taking strategies used by President Jokowi and Boy William in Nebeng Boy youtube channel. The researchers used theory by Stenstrom as cited in Yanti (2017). This theory describes three types namely Taking the turn (starting up, take over, interrupting), Holding the turn (filled pause, silent pause, meta-comments), Yielding the turn (prompting, appealing, giving up. This type of research was qualitative method, the researchers used an approach qualitative descriptive to describe the turn-taking strategies that included in conversation between Mr. Jokowi and Boy William in Nebeng Boy YouTube Channel, since the data the researcher did not use numeric or statistic form in the data analysis. The result of this research showed that there are 28 data with the different percentage such as; Hesitant Start (4%), Clean Start (4%), Uptakes (4%), Link (4%), Alert (4%), Meta-Comments (-), Filled Pause (10%), Silent Pause (17%), Repetition (39%), Prompting (4%), Appealing (6%), Giving up (4%). It can be concluded, that the most dominant is Repetition that occurs 11 times from 28 data.